Validity of the optical nerve sheath diameter by ultrasonography for the diagnosis of intracranean hypertension in severe craneoencephalic trauma - Zamora-Cueva, Rodrigo (2021)
Objetive: To determine the validity of the diameter of the optic nerve sheath by ultrasound for the diagnosis of intracranial hypertension in patients with severe traumatic brain injury. Material and methods: A diagnostic test study was carried out in 43 patients with suspected intracranial hypertension secondary to severe traumatic brain injury, who fulfilled the diagnostic criteria according to the "Clinical Decision Rule" based on clinical and tomographic findings, then were made measurements of the optic nerve sheath by ultrasound at the Regional Teaching Hospital of Trujillo between May 2019 -January 2020. Results: From a total of 43 patients, when processing the data using the ROC curve, a cut point of the diameter of the optic nerve sheath of 6.05 mm was obtained, equivalent to intracranial hypertension, with an area under the curve (AUC) of 0.776 (P = 0.004); sensitivity, specificity, positive and negative prediction value of 82.76%, 57.14%, 80% and 61.54% respectively. No significant differences were found between the 2 groups in terms of sex, age, anisocoria and diastolic arterial hypotension. Conclusions: The diameter of the optic nerve sheath measured by ultrasound is valid for the diagnosis of intracranial hypertension secondary to severe traumatic brain injury.